Inflammasome Activation Contributes to Interleukin-23 Production in Response to Clostridium difficile - Carrie A. Cowardin (American Society for Microbiology, 2015)
ABSTRACT   Clostridium difficile is the most common hospital-acquired pathogen, causing antibiotic-associated diarrhea in over 250,000 patients annually in the United States. Disease is primarily mediated by toxins A and B, which induce potent proinflammatory signaling in host cells and can activate an ASC-containing inflammasome. Recent findings suggest that the intensity of the host response to infection correlates with disease severity. Our lab has identified the proinflammatory cytokine interleukin-23 (IL-23) as a pathogenic mediator during C. difficile infection (CDI). The mechanisms by which C. difficile induces IL-23, however, are not well understood, and the role of toxins A and B in this process is unclear. Here, we show that toxins A and B alone are not sufficient for IL-23 production but synergistically increase the amount of IL-23 produced in response to MyD88-dependent danger signals, including pathogen-associated molecular patterns (PAMPs) and host-derived damage associated molecular patterns (DAMPs). Danger signals also enhanced the secretion of IL-1β in response to toxins A and B, and subsequent IL-1 receptor signaling accounted for the majority of the increase in IL-23 that occurred in the presence of the toxins. Inhibition of inflammasome activation in the presence of extracellular K+ likewise decreased IL-23 production. Finally, we found that IL-1β was increased in the serum of patients with CDI, suggesting that this systemic response could influence downstream production of pathogenic IL-23. Identification of the synergy of danger signals with toxins A and B via inflammasome signaling represents a novel finding in the mechanistic understanding of C. difficile-induced inflammation. IMPORTANCE Clostridium difficile is among the leading causes of death due to health care-associated infection, and factors determining disease severity are not well understood. C. difficile secretes toxins A and B, which cause inflammation and tissue damage, and recent findings suggest that some of this tissue damage may be due to an inappropriate host immune response. We have found that toxins A and B, in combination with both bacterium- and host-derived danger signals, can induce expression of the proinflammatory cytokines IL-1β and IL-23. Our results demonstrate that IL-1β signaling enhances IL-23 production and could lead to increased pathogenic inflammation during CDI.